EVALUATION AND IMPROVEMENT OF TELEPHONY CALL CENTER BUSINESS PROCESS AT PT. BXX - Farrel Ravindra, Muhammad
This research focuses on addressing the problem of uneven queuing distribution among call center agents in PT. BXX, which indicates a flaw in the current business process of the organization. The study utilizes the business process reengineering (BPR) method, involving the mapping using service blueprint, analysis, and development of a new business process to resolve the issue. The data collection process incorporates various sources such as company reports, observations, and interviews with the call center manager to gain insights into the challenges and potential solutions. The analysis reveals 14 necessary but non-value added activities and 8 value added activities within the current business process. A potential fail point is identified where instances of the product owner failing to fulfill the caller's request within the expected time resulting in repeat calls. Repeat callers are required by the company to be assigned to the previous agent they interacted with to save time. However, this can lead to the accumulation of long queues for certain agents, resulting in increased average waiting time and a higher likelihood of abandonment. The proposed to-be business process suggests incorporating a progress update process and modifying the queuing process to include a callback option. These solutions aim to reduce repeat calls, inform callers about their requests, and prevent queue buildup. The proposed changes are expected to enhance queuing distribution, reduce waiting times, and minimize call abandonment. Overall, this research contributes to the field of business process management by applying BPR to resolve the issue of uneven queuing in BXX's call center. The findings serve as a reference for organizations facing similar challenges, providing insights into improving efficiency and customer service through business process reengineering.